Harnessing Information Technology in Learning: Exploring Emerging Trends and Innovative Approaches - Vedpathak, Mangesh; Prashant MITHARI (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
In today's education landscape, incorporating information technology is crucial for changing teaching methods and improving learning experiences. This paper delves into the ever-evolving landscape of pedagogy, shedding light on emerging trends that are reshaping educational practices and unique approaches. This paper examines the evolving use of information technology in education, focusing on current trends like multi-agent educational systems, virtual worlds, and web-based learning. By synthesizing insights from scholarly literature and recent research, this paper identifies, and examines key trends such as personalized learning, competency-based education, and immersive learning experiences. Through an imaginative exploration of these innovative methods, this paper aims to highlight their potential to transform teaching and learning. Through a creative exploration of these innovative, and approaches, this paper aims to inspire educators and policymakers to embrace new paradigms in teaching and advanced learning. Drawing from academic literature and recent studies, this paper offers insights into the theoretical basis, practical applications, and future implications of information technology in education. By combining varied viewpoints and presenting innovative ideas, this paper strives to encourage educators and policymakers to embrace the transformative power of information technology in shaping the future of education.